Layer-by-layer deposition of chitosan nanoparticles as drug-release coatings for PCL nanofibers. (4th December 2018) - Sydow, Steffen; de Cassan, Dominik; Hänsch, Robert; Gengenbach, Thomas R.; Easton, Christopher D.; Thissen, Helmut; Menzel, Henning
Abstract : Modified PCL fiber mat with fluorescently labeled CS-TPP nanoparticle system via LbL dip coating. Abstract : Nanogels were prepared by ionotropic gelation of chitosan (CS) with tripolyphosphate (TPP). The use of such nanogels to prepare coatings by layer-by-layer deposition (LbL) was studied. The nanogels were characterized in terms of particle size, zeta-potential and stability. Nanogel suspensions were used to build polyelectrolyte multilayers on silicon wafers and on PCL fiber mats by LbL-deposition. Three different polysaccharides were used as polyanions, namely chondroitin sulfate, alginate and hyaluronic acid. The ellipsometric thickness was demonstrated to depend significantly on the type of polyanion. XPS analysis with depth profiling further substantiated the differences in the chemical composition of the films with the different polyanions. Furthermore, XPS data clearly indicated a strong penetration of the polyanions into the CS-TPP layer, resulting in a complete exchange and release of the TPP ions. The LbL-deposition also was studied with PCL fiber mats, which were modified with a chitosan-PCL-graft polymer and alginate. The possibility to create graded coatings on the fiber mats was shown employing fluorescently labelled CS–TPP nanoparticles. The potential of the coatings as drug delivery system for therapeutic proteins was exemplified with the release of Transforming Growth Factor β3 (TGF-β3 ). The CS–TPP nanogels were shown to encapsulate and release therapeutic proteins. In combination with the layer-by-layer deposition they will allow the creation of PCL fiber mat implants having with drug gradients for applications at tissue transitions.